The geostatistical approach for structural and stratigraphic framework analysis of offshore NW Bonaparte Basin, Australia - Ali Wahid, Ahmed Mohamed Ahmed Salim, Gamal Ragab Gaafar, Wan Is, . (2016)
Geostatistics or statistical approach is based on the studies of temporal and spatial trend, which depend upon spatial relationships to model known information of variable (s) at unsampled locations. The statistical technique known as kriging was used for petrophycial and facies analysis, which help to assume spatial relationship to model the geological continuity between the known data and the unknown to produce a single best guess of the unknown.